First Observations of Large Scale Traveling Ionospheric Disturbances Using Automated Amateur Radio Receiving Networks. Issue 5 (1st March 2022) - Frissell, Nathaniel A.; Kaeppler, Stephen R.; Sanchez, Diego F.; Perry, Gareth W.; Engelke, William D.; Erickson, Philip J.; Coster, Anthea J.; Ruohoniemi, J. Michael; Baker, Joseph B. H.; West, Mary Lou
Abstract: We demonstrate a novel method for observing Large Scale Traveling Ionospheric Disturbances (LSTIDs) using high frequency (HF) amateur radio reporting networks, including the Reverse Beacon Network (RBN), Weak Signal Propagation Reporter Network (WSPRNet), and PSKReporter. LSTIDs are quasi‐periodic variations in ionospheric densities with horizontal wavelengths >1, 000 km and periods between 30 and 180 min. On Nov 3, 2017, LSTID signatures were observed simultaneously over the continental United States in amateur radio, SuperDARN HF radar, and GNSS Total Electron Content with a period of ∼2.5 hr, propagation azimuth of ∼163°, horizontal wavelength of ∼1680 km, and phase speed of ∼1, 200 km hr −1 . SuperMAG SME index enhancements and Poker Flat Incoherent Scatter Radar measurements suggest the LSTIDs were driven by auroral electrojet intensifications and Joule heating. This novel measurement technique has applications in future scientific studies and for assessing the impact of LSTIDs on HF communications. Plain Language Summary: Large Scale Traveling Ionospheric Disturbances (LSTIDs) are variations in the ionosphere with wavelengths greater than 1, 000 km, periodicities between 30 min and 3 hr, and speeds greater than about 1, 400 km per hour. Auroral zone disturbances are generally cited as the energy source for LSTIDs. In this paper, we show for the first time that LSTIDs can cause variations in the distances amateur (ham) radio operators can communicate using data from the Reverse Beacon Network (RBN), Weak Signal Propagation Reporter Network (WSPRNet), and PSKReporter amateur radio networks. The LSTID signatures in the amateur radio data are in excellent agreement with LSTID observations from two well‐established instruments: the Blackstone, Virginia SuperDARN radar and a large scale network of GNSS based ionospheric Total Electron Content receivers. The observed LSTIDs appear 2–3 hr after auroral zone disturbances are detected by ground magnetometers in the SuperMAG network and the Poker Flat Incoherent Scatter Radar (PFISR) in Alaska. Results suggest that auroral zone disturbances were the ultimate cause of the observed LSTIDs. This paper provides a foundation for using large‐scale, crowd‐sourced amateur radio observations of LSTIDs as a new method for the study of LSTIDs. Key Points: Amateur radio data provides a new method for studying Large Scale Traveling Ionospheric Disturbances and HF communications impacts Large Scale Traveling Ionospheric Disturbances are seen for the first time simultaneously in amateur radio, SuperDARN, and GNSS TEC data Observed midlatitude Large Scale Traveling Ionospheric Disturbances are likely driven by auroral zone electrojet surges and Joule heating